1989
DOI: 10.1111/j.1365-2125.1989.tb03545.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gastric mucosal bleeding with doses of aspirin used for prophylaxis and its reduction by ranitidine.

Abstract: 1. We evaluated injury to the human gastric mucosa caused by low doses of aspirin and its prophylaxis by ranitidine. On two separate occasions, 30 subjects took aspirin 300 mg daily for 12 days either with or without ranitidine 150 mg, 30 min before aspirin. This dose of aspirin caused more than a 5 fold increase in gastric bleeding, from control values of 0.5 microliters 10 min‐1 (95% confidence limits 0.3‐ 0.8 microliters 10 min‐1) to 2.8 microliters 10 min‐1 (1.9‐4.1 microliters 10 min‐1, P less than 0.01) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The H2RA ranitidine, at a dose of 150 mg/day, significantly increased intragastric pH and reduced the amount of gastric bleeding in subjects taking ASA 300 mg/day. 82 Similar results were seen in 2 further trials in volunteers. 83 Despite a single endoscopic study demonstrating that H2RAs at double the usual dose may be effective compared with placebo, studies comparing high doses of H2 blockers to misoprostol or PPIs for the prevention of NSAID ulcers are not available.…”
Section: Treatment and Prevention Of Asa-and Nsaid-related Gastroduodsupporting
confidence: 75%
“…The H2RA ranitidine, at a dose of 150 mg/day, significantly increased intragastric pH and reduced the amount of gastric bleeding in subjects taking ASA 300 mg/day. 82 Similar results were seen in 2 further trials in volunteers. 83 Despite a single endoscopic study demonstrating that H2RAs at double the usual dose may be effective compared with placebo, studies comparing high doses of H2 blockers to misoprostol or PPIs for the prevention of NSAID ulcers are not available.…”
Section: Treatment and Prevention Of Asa-and Nsaid-related Gastroduodsupporting
confidence: 75%
“…Hawkey and colleagues found that the gastric microbleeding induced by aspirin was decreased by approxi mately 50% when patients were given raniti dine. 150 mg. 30 minutes before the aspirin [15]. Famotidine also protected against aspirininduced microbleeding [16).…”
Section: Protection Against Gastric Mucosal Damage Reducing Acidity Bmentioning
confidence: 93%
“…PPIs block the final step of acid production and lead to prolonged acid suppression. H 2 RAs had also demonstrated a gastro-protective effect [28,42]. However, PPIs appeared to be superior to H 2 RA for prevention of peptic ulcer, and co-treatment with angiotensin II type 1 receptor blocker or ACE inhibitor appeared to further reduce peptic ulcer [43].…”
Section: Status Of Gastro-prophylaxismentioning
confidence: 95%